2014
DOI: 10.1155/2014/406462
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Fair Spectrum Allocation and Reduced Spectrum Handoff in Wireless Sensor Networks: Modeling via Biobjective Optimization

Abstract: This paper considers the problem of centralized spectrum allocations in wireless sensor networks towards the following goals: (1) maximizing fairness, (2) reflecting the priority among sensor data, and (3) avoiding unnecessary spectrum handoff. We cast this problem into a multiobjective mixed integer nonconvex nonlinear programming that is definitely difficult to solve at least globally without any aid of conversion or approximation. To tackle this intractability, we first convexify the original problem using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The authors explained the proportional fairness using the NBS concept. There are also many studies on the proportional fair resource allocation in wireless sensor networks, such as [18].…”
Section: Related Workmentioning
confidence: 99%
“…The authors explained the proportional fairness using the NBS concept. There are also many studies on the proportional fair resource allocation in wireless sensor networks, such as [18].…”
Section: Related Workmentioning
confidence: 99%
“…According to spectrum, survey conducted by the Federal Communication Commission (FCC) has indicated that the actual licensed spectrum is not utilized properly for various time, frequency, and geographical locations [1]. Also the demand of allocating and using the radio frequency spectra is rapidly growing due to increasing number of wireless applications [2]. An unlicensed user or secondary user may utilize this band when licensed user is absent.…”
Section: Introductionmentioning
confidence: 99%